A copula-based fuzzy interval-random programming approach for planning water-energy nexus system under uncertainty. (1st April 2020) - Yu, L.; Xiao, Y.; Jiang, S.; Li, Y.P.; Fan, Y.R.; Huang, G.H.; Lv, J.; Zuo, Q.T.; Wang, F.Q.
Abstract: Water and energy are closely linked and restrict each other, which has become major restraints to urban development associated with constricted water resources availability, increased electricity demand and limited environmental capacity. In this study, a copula-based fuzzy interval-random programming method is proposed through integration of copula-based random programming, interval-parameter programming and fuzzy possibilistic programming. It can both handle random, interval and fuzzy information and reflect system joint-risk existing in the water-energy nexus system of Henan Province, China. A class of copulas associated with different water resources availability and electricity consumption scenarios as well as various uncertainties are examined. Results disclose that: a) uncertainties and scenarios employed to water resources, electricity demand and other module parameters can generate prominent impacts on future water-energy nexus system; b) the percentage of electricity by coal-fired power can decrease by [1.8, 2.6] % under low water resources availability scenario compared to high water resources availability scenario. Findings can provide optimal electricity-supply schemes under the conflicts among economic objective, water resources shortage and electricity demand as well as environmental requirement. Highlights: A copula-based fuzzy interval-random programming method is developed. It is applied to the water-energy nexus system of Henan Province, China. It can deal with multi-uncertainty and reflect system joint-risk. Various copulas associated with different joint-interaction scenarios are analyzed. Findings can provide decision supports for other water-energy nexus systems.